Efektifitas Pemberian Terapi Pursed Lips Breathing Terhadap Status Oksigenasi Anak Dengan Pneumonia: Effectiveness of Pursed Lips Breathing Therapy on Children's Oxygenation Status Oxygenation Status of Children With Pneumonia - Yunita Muliasari; Iin Indrawati (Fakultas Keperawatan Universitas Andalas, 2017)
Background: Pneumonia is the second most common disease that causes death in children under five in the world. Symptoms that appear in the case of Pneumonia are acute respiratory problems that need to be handled appropriately. The aim of this research are to identify the effect of pursed lips breathing therapy through tongue blowing activity on the oxygenation status of preschoolers with Pneumonia. Method: The sampling technique is purposive random sampling with 36 people consisting of 18 intervention groups and 18 control groups. Data were analyzed using univariate and bivariate tests. Result: The results showed a significant difference between oxygenation status before and after intervention with tongue blowing therapy (PLB), namely p = 0.045 on respiratory frequency (RR) and p = 0.037 to saturation oxygen. Recommendation: The results of this study can add alternatives to independent nurse interventions in dealing with pediatric patients who have pneumonia or with oxygenation disorders.